Target Firm Tobin’s Q and Acquirer Announcement Returns : Evidence from U.S. Mergers and Acquisitions, 2009–2024 - Oikari, Jaakko (My University, 2026)
The Q hypothesis of corporate takeovers proposes that higher acquirer announcement returns are connected to the acquisition of undervalued target firms. However, the generalizability of the relationship between target firm Tobin's Q and acquirer stock returns has been increasingly contested in modern M&A market conditions. This thesis investigates whether target firm Tobin's Q has retained predictive power for acquirer cumulative abnormal returns in the post-financial-crisis United States M&A market. The study derives from the Q-theory of takeovers as its central theoretical benchmark, sup-plemented by market efficiency, signalling theory, agency theory and managerial hubris, and behavioral finance perspectives. The approximate Tobin’s Q is applied as the primary measure of target firm valuation, with payment method incorporated as the main control variable based on information asymmetry theory. The sample consists of 344 completed public-to-public M&A transactions in the United States announced between 2009 and 2024, with stock prices obtained from the Polygon.io API and financial statements data extracted from SEC EDGAR database. Event-study methodology is applied across five event windows using mean- and market adjusted benchmark models, complemented by cross-sectional OLS regressions with industry and year fixed effects and heteroskedasticity-robust standard-errors. The null hypothesis is not rejected: target firm Tobin's Q does not significantly predict acquirer cumulative abnormal returns in any specifications. Payment method occurs as the dominant cross-sectional predictor of acquirer stock returns, with stock-paid acquisitions generating significantly more negative returns than cash-paid deals in all specifications. The findings are interpreted through a regime-conditional framework: the null finding on To-bin’s Q is consistent with elevated equity market valuations, growth-versus-value stock cycle, and managerial miscalibration on the firm valuation which all characterise the sample period of 2009-2024, rather than a disconfirmation of the Q hypothesis itself. The Tobin’s Q-CAR rela-tionship is expected to reimpose itself in future market environments closer to historical fun-damental benchmarks. Conversely, the robustness of the payment method effect, confirms that adverse selection remains a solid cross-sectional driver of acquirer wealth effects across decades.

Yrityskauppoihin liittyvä Q-hypoteesi esittää, että ostajayhtiön korkeammat osaketuotot yrityskaupan julkistushetkellä liittyvät aliarvostettujen kohdeyhtiöiden hankintaan. Kohdeyhtiön Tobinin Q:n ja ostajayhtiön osaketuottojen välinen yhteys on kuitenkin modernilla M&A-markkinalla kiistanalainen. Tämä pro gradu -tutkielma tarkastelee, onko kohdeyhtiön Tobinin Q säilyttänyt kykynsä ennustaa ostajayhtiön kumulatiivisia osaketuottoja yrityskaupan julkistuksen yhteydessä finanssikriisin jälkeisessä Yhdysvalloissa vuosina 2009–2024. Tutkimuksen teoreettisena viitekehyksenä toimii yrityskauppojen Q-hypoteesi, jota täyden-netään markkinatehokkuuden, signalointiteorian, agenttiteorian ja käyttäytymistieteellisen rahoituksen näkökulmilla. Tobinin Q toimii kohdeyhtiön markkina-arvostuksen mittarina, ja transaktion maksutapa sisällytetään analyysiin keskeisenä kontrollimuuttujana informaation epäsymmetriaan liittyvien teorioiden pohjalta. Aineisto koostuu 344 julkisten yhtiöiden välisestä yrityskaupasta Yhdysvalloissa. Osakekurssi-data on kerätty Polygon.io-rajapinnasta ja tilinpäätöstiedot SEC EDGAR -tietokannasta. Tutkimuksessa hyödynnetään tapahtumatutkimusmenetelmää viidessä tapahtumaikkunassa sekä keskiarvo- ja markkinakorjattuja malleja. Lisäksi analyysia täydennetään lineaarisella OLS-regressiomallilla, jossa huomioidaan toimiala- ja vuosikohtaiset kiinteät vaikutukset sekä het-eroskedastisuuden kestävät testaukset (HC3, VIF ja Breusch–Pagan). Tulosten perusteella nollahypoteesia ei voida hylätä, sillä kohdeyhtiön Tobinin Q ei ennusta luotettavasti ostajayhtiön kumulatiivisia osaketuottoja missään tapahtumaikkunassa. Sen sijaan transaktion maksutapa osoittautuu merkittäväksi selittäjäksi: omilla osakkeilla rahoite-tut yrityskaupat tuottavat systemaattisesti negatiivisempia osaketuottoja kuin käteisellä to-teutetut transaktiot. Tuloksia tulkitaan regiimiriippuvaisessa viitekehyksessä. Q-hypoteesin heikko toimivuus on yhdenmukainen tutkimusjakson korkeiden osakemarkkina-arvostusten, kasvuosakkeiden korostuneen suosion ja johdon mahdollisten arvostusvirheiden kanssa. Tulokset eivät siten välttämättä kumoa Q-hypoteesia, vaan viittaavat siihen, että Tobinin Q:n ja ostajayhtiön osaketuottojen välinen yhteys voi palautua markkinaolosuhteiden normalisoituessa. Samalla maksutavan vahva vaikutus tukee näkemystä siitä, että haitallinen valikoituminen säilyy kes-keisenä ostajayhtiön arvonsiirtoa selittävänä tekijänä yrityskaupoissa.
Keywords: objectives; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance